Stylistic Analysis Of Deictic Expressions Used on EFL Written Essay Grade III at English Department at FKIP UHN Pematangsiantar - Bertaria Sohnata Hutauruk (Universitas Bunda Mulia, 2018)
Deixis is a technical term for one of the most basic things we do with utterance. When we ask someone, “come here!” We are using a context in the utterance, such as who is speaking to whom, what relation they have, the time or place of speaking, the gesture of the speaker and what status the interaction participants have. Conncerning to the background of the research, there are two questions raised in this research they are: (1) What deictic expressions found on EFL ’Written Essay Grade III At English Department At FKIP UHN Pematangsiantar, (2) What are the possible interpretation appeared from the deictic expressions found n EFL ’Written Essay Grade III At English Department At FKIP UHN Pematangsiantar. The researcher used some theories related with deixis such as Yule (1995, p. 9), Levinson (1983, p. 55), Lyon (1983, p. 275), and James (1983, p. 63). This research is conducted using a descriptive qualitative research.There are 70 students (academic year 2015) taking Professional Development for English Teacher subject at English Department at FKIP UHN Pematangsiantar. The researcher asked the students to perform and tell their expectations after being an English teacher in the future. After doing the analysis from the whole data of the research, the writer found the research findings: there are some types of deixis in the students’ writing. Person deixis is used in the students’ writing because the writer shows their thinking and their understanding. In the person deixis is used in the text, first person deixis is most dominant that the researcher found in the text. It is because of the writer tells their willing to be a teacher in the future. As a whole, after the data have been analyzed by the researcher, there are some types of deixis in the students’ writing. Person deixis is used in the students’ writing because the writer shows their thinking and their understanding. In the person deixis is used in the text, first person deixis is most dominant that the researcher found in the text. It is because the writers tell their willingness to be teachers in the future.Keywords: deixis, written essay, stylistic analysis, deictic expressions